Manajemen Kegiatan Keagamaan Di Panti Rehabilitasi Yayasan Medan Plus Kota Pinang Dalam Mengatasi Kecanduan Narkoba - Saipul Amri Siregar; Annai Saburi (Universitas Cokroaminoto Yogyakarta, 2026)
This study aims to examine how to manage religious activities at the Medan Plus Kotapinang Foundation Rehabilitation Center as part of drug addiction prevention efforts. This qualitative case study analyzed data obtained through interviews, observations, and documentation. The results showed that the implementation of religious activities that were systematically designed, planned, and sustainable played a role in shaping positive self-concepts in residents through various Islamic religious activities. The management involved four main components: mentors, residents, religious materials, and guidance methods, both group and individual. The religious atmosphere created provided significant support for the recovery process and the formation of a healthier self-concept. Management of religious activities has become an important element in the rehabilitation of drug addicts.